Optimalisasi Pengelolaan Zakat di Kecamatan Sedong Kabupaten Cirebon - Teguh Lesmana; Mohammad Ridwan; Dini Selasi; Bambang Firmansyah (Muttaqien Publishing, Lembaga Penelitian dan Pengabdian kepada Mayarakat (P3M) STAI DR. KH.EZ. Muttaqien Purwakarta, 2024)
In various cultures, the values of sharing and concern for others play a crucial role. In the context of Islam, the concept of zakat promotes social justice and well-being. This research focuses on the management of zakat in the Sedong District, Cirebon Regency, to understand its effectiveness. The study emphasizes the importance of fair recipient selection, transparency in fund utilization, and the empowerment of beneficiaries' economies. Community participation, from collection to evaluation, is key to addressing the complexity of zakat management. Involving the community can make zakat a more potent tool in reducing poverty and fostering social inclusion. This research aims to contribute to the understanding of the role of zakat in alleviating poverty and building communities in the Sedong District. The findings can be used to enhance zakat programs, making it a more effective instrument in improving well-being and social inclusion in the region.